Efeito cardioprotetor do exercício físico na sobrecarga β-adrenérgica cardíaca induzida por isoproterenol - Serra, Andrey Jorge [UNIFESP] (2009)
Background: Sustained β-adrenoreceptor activation promotes cardiac hypertrophy and cellular injury. Aims: To evaluate the cardioprotective effect of exercise on damage induced by β-adrenergic hyperactivity. Methods: Male Wistar rats were randomised into four groups (n = 8 per group): sedentary non-treated control (C), sedentary treated with isoproterenol 0.3 mg/kg/day administered subcutaneously for 8 days (I), exercised non-treated (E) and exercised plus isoproterenol administered during the last eight days of exercise (IE). Exercised animals ran on a treadmill for 1 h daily 6 times a week for 13 weeks. Results: Isoproterenol caused increases in left ventricle (LV) wet and dry weight/body weight ratio, LV water content and cardiomyocyte transverse diameter. Additionally, isoproterenol induced severe cellular lesions, necrosis, and apoptosis, increased collagen content and reduced capillary and fibre fractional areas. Notably, all of these abnormalities were completely prevented by exercise. Conclusion: Our data have demonstrated that complete cardioprotection is possible through exercise training; by preventing β-adrenergic hyperactivity-induced cardiac hypertrophy and structural injury. Abstracts do artigo 2: To test the hypothesis that exercise training can prevent the myocardial dysfunction and to inhibit the left ventricular (LV) remodeling induced by β-adrenergic hyperactivity, Wistar male rats were assigned to four groups: sedentary non-treated (CON), sedentary isoproterenol- treated (ISO), exercised non-treated (EX), and exercised plus isoproterenol (I+E). Echocardiography, hemodynamic and isolated papillary muscle were used for functional evaluations. Real time RT-PCR and western blot were used to quantify TNF-α, IL-6, IL-10 and TGF-β1 in the tissue. The nuclear NF-кB expression was evaluated by immunohistochemical staining. The ISO rats showed a concentric hypertrophy of LV. These animals exhibited marked increases in LV end-diastolic pressure and impaired myocardial performance in vitro by reducing the developed tension and maximum rate of tension increase and decrease, as well as worsened recruitment of the Frank-Starling mechanism. Both gene and protein levels of TNF-α and IL-6 as well as the TGF-β1 mRNA were also increased. In addition, the nuclear NF-kB expression in the ISO group was significantly raised. In the I+E group, the exercise training (i) prevented LV hypertrophy, (ii) improved myocardial contractility, (iii) avoided the increase of pro-inflammatory cytokines and improved IL-10 levels, and (iiii) attenuated the increase of TGF-β1 mRNA. Thus, exercise training in a model of β-adrenergic hyperactivity can avoid the adverse remodeling of LV and improve the myocardial contractile. It appears likely that the cardioprotection is related to beneficial effects of exercise on balance between pro- and anti-inflammatory cytokines, and mitigates the expressions of TGF-β1